Preliminary study on biohydrogen production by bacteria from sago waste - Mohamad Puad, Noor Illi; Sulaiman, Sarina; Azmi, Azlin Suhaida; Shamsudin, Yusra; Mel, Maizirwan (2014)
Sago waste which has not been fully utilized is a potential substrate for biotechnology production. In lieu of that, a study focused on utilizing the waste to produce biohydrogen as the green- technology product was conducted. This study is concerned with the hydrogen gas production by Escherichia coli (E. coli) using dark fermentation by utilizing sago waste as the substrate. Acid pre-treatment process for sago waste was executed and the content of reducing sugar was analysed using Dinitrosalicylic acid (DNS) method. The glucose content after pre-treatment process was 2.150 g/L when treated at the temperature of 90C for 40 minutes. Dark fermentation process was performed for 14 hours and three factors which were inoculum size (10-30%), pH (6-8) and temperature (28-40C) were investigated. The design of experiment was done using central composite design (Design Expert v6.0.8). Maximum yield of 2.22 mol H2/ mol glucose was obtained from Run 8 at processing parameters of pH 6, temperature of 40C and 30% inoculum size. The findings of this study can be applied in production of biohydrogen at a wider range of parameters (pH, temperature, inoculum size) for further studies.